Paste additive for lead-acid storage battery pole plate
By adding graphene and nano-silicon powder to the lead-acid battery plate and combining with the modified liquid treatment, the problem of lead sulfate crystallization on the surface of the lead-acid battery plate is solved, the internal resistance of the battery is reduced, and the cycle life and charging and discharging capacity of the battery are improved.
Patent Information
- Application Number
- CN202411881298.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-21
AI Technical Summary
When the lead-acid battery is suspended due to force majeure or the temperature is high, large particles of lead sulfate crystals are easily formed on the surface of the electrode plate, resulting in an increase in the internal resistance of the battery, a decrease in the CCA of the meter, a fast self-discharge, and a decrease in service life.
Graphene and nano-silica powder are used as lead-acid battery plate paste additives, with the addition of graphene from 0.12 to 0.22% and the addition of nano-silica powder from 0.53 to 0.65%. The performance of graphene is optimized by the modification liquid treatment.
It significantly inhibits the formation of sulfuric acid crystallization, reduces the internal resistance of the battery, improves the CCA of the battery meter, extends the cycle life of the battery, improves the charging and discharge reception ability, and meets consumers' demand for the long-lived surface of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lead-acid batteries, and in particular to a paste additive for lead-acid battery polar plates. Background Art
[0002] Incompletely formed batteries are placed statically, that is, the lead-acid battery is not charged and formed after the electrolyte is injected, and the formation process is suspended due to force majeure factors such as high temperature or power outage. Large particles of lead sulfate crystals are easily formed on the surface of the plate. Coarse lead sulfate crystals are easy to adsorb each other to form small crystals, and even snowball to form a whole crystal film covering the surface of the plate. These are all inert crystals. Coarse lead sulfate crystals are easy to block the pores of active substances, hinder the penetration and diffusion of electrolytes, increase the internal resistance of the battery, and hinder the conversion of lead sulfate into lead dioxide and spongy lead during battery formation. The lead sulfate is reversible during the battery injection electrolyte formation process, and the lead sulfate crystals on the plate surface are partially irreversible, the battery formation conversion effect is poor, and the battery card meter CCA is reduced. Due to the incomplete conversion of lead sulfate, the lead sulfate crystals cover the surface of the plate. The difference in electrolyte concentration between the inside and outside of the battery plate during the storage period before the battery is loaded and used will accelerate self-discharge, the battery open circuit voltage drops quickly, and the battery needs to be recharged frequently before leaving the warehouse.
[0003] After the battery is installed and used, the crystallization of lead sulfate on the surface of the plate accelerates, the lead sulfate crystals cover the surface of the plate lead paste, and even enter the inside of the plate and cover the surface of the grid, gradually vulcanizing. The working area of the grid and lead paste reaction will be reduced, the binding force between the active substances of the grid and lead paste will be reduced, the active substances are easy to soften and fall off, the grid may deform and break, the battery is easy to heat up and lose water faster, and the battery life is reduced. Summary of the invention
[0004] In view of the defects of the prior art, the object of the present invention is to provide a paste additive for lead-acid battery plates to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution: The invention provides a paste additive for a lead-acid battery plate, comprising graphene and nano silicon powder, wherein the addition amount of the graphene is 0.12-0.22% by weight of the lead powder of the positive electrode lead paste and 0.1%-0.2% by weight of the lead powder of the negative electrode lead paste; the addition amount of the nano silicon powder is 0.53-0.65% by weight of the lead powder of the positive electrode lead paste and 0.5%-0.6% by weight of the lead powder of the negative electrode lead paste.
[0006] Preferably, the graphene is multilayer graphene with a thickness of less than 10 nm, wherein carbon atoms are tightly stacked in an ABC manner to form a benzene ring structure; The purity of nano silicon powder reaches more than 99.999%, the particle size is evenly distributed in 2~4nm, and the specific surface area is 800m 2 above.
[0007] Preferably, the graphene is further treated with a modifying liquid, and the specific treatment method is: Add 1-3 parts of silane coupling agent, 2-4 parts of yttrium oxide and 2-3 parts of nano calcium carbonate to 5-8 parts of regulator and stir evenly to obtain modified liquid; add graphene to a sufficient amount of modified liquid and stir for modification treatment, filter and dry after stirring.
[0008] Graphene is treated with a specific modified liquid to optimize battery cycle times and discharge capacity, thereby improving product performance.
[0009] Preferably, the stirring speed of the stirring modification treatment is 450-550 r / min, and the stirring is for 1 hour.
[0010] Preferably, the silane coupling agent is silane coupling agent KH550.
[0011] Preferably, the regulating solution comprises 1-3 parts of sodium silicate solution, 2-4 parts of lanthanum chloride solution and 2-4 parts of nano titanium dioxide.
[0012] Preferably, the mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the lanthanum chloride solution is 4-7%.
[0013] Preferably, the positive electrode lead paste includes 50-55 parts of lead powder, 2-3 parts of sulfuric acid, 15-16 parts of water, 2-5 parts of red lead, and 4-7 parts of carbon fiber.
[0014] Preferably, the negative electrode lead paste is prepared from the following raw materials by weight: 0.1-0.2 parts of lignin, 0.2-0.3 parts of acetylene black, 0.4-0.6 parts of barium sulfate, 3-4 parts of sulfuric acid, 12-14 parts of water, and 55-60 parts of lead powder.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The graphene and nano silicon powder of the present invention are added into the pole plate as additives of the lead-acid battery pole plate paste to make double-nano-type pole plates to produce lead-acid batteries. The pole plate and the paste are cured to form double-nano crystals. The double-nano crystals can significantly inhibit the formation of sulfuric acid crystals, inhibit the clustering and adsorption of lead sulfate crystals to form coarser crystals and crystal films, thereby ensuring the static formation effect of the incompletely formed battery, reducing the internal resistance of the battery, increasing the CCA (conductance value) of the battery card, reducing the self-discharge rate of the battery, and the battery is installed on a vehicle for use. The cyclic conversion of lead sulfate is almost completely reversible, which greatly improves the charge and discharge acceptance capacity and the cycle life, and further meets the demand of contemporary consumers for the longevity of batteries. DETAILED DESCRIPTION
[0016] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] A paste additive for a lead-acid battery plate of the present embodiment comprises graphene and nano silicon powder, wherein the addition amount of graphene is 0.12-0.22% by weight of the positive electrode lead paste lead powder and 0.1%-0.2% by weight of the negative electrode lead paste lead powder; the addition amount of nano silicon powder is 0.53-0.65% by weight of the positive electrode lead paste lead powder and 0.5%-0.6% by weight of the negative electrode lead paste lead powder.
[0018] The graphene of this embodiment is multi-layer graphene with a thickness of less than 10 nm, in which carbon atoms are tightly stacked in an ABC manner to form a benzene ring structure; The purity of nano silicon powder reaches more than 99.999%, the particle size is evenly distributed in 2~4nm, and the specific surface area is 800m 2 above.
[0019] The graphene of this embodiment is also treated with a modifying liquid, and the specific treatment method is as follows: Add 1-3 parts of silane coupling agent, 2-4 parts of yttrium oxide and 2-3 parts of nano calcium carbonate to 5-8 parts of regulator and stir evenly to obtain modified liquid; add graphene to a sufficient amount of modified liquid and stir for modification treatment, filter and dry after stirring.
[0020] The stirring speed of the stirring modification treatment in this embodiment is 450-550 r / min, and the stirring is for 1 hour.
[0021] The silane coupling agent of this embodiment is silane coupling agent KH550.
[0022] The regulating solution of this embodiment uses 1-3 parts of sodium silicate solution, 2-4 parts of lanthanum chloride solution and 2-4 parts of nano titanium dioxide.
[0023] The mass fraction of the sodium silicate solution in this embodiment is 2-5%; the mass fraction of the lanthanum chloride solution is 4-7%.
[0024] The positive electrode lead paste of this embodiment includes 50-55 parts of lead powder, 2-3 parts of sulfuric acid, 15-16 parts of water, 2-5 parts of red lead, and 4-7 parts of carbon fiber.
[0025] The negative electrode lead paste of this embodiment is prepared from the following raw materials by weight: 0.1-0.2 parts of lignin, 0.2-0.3 parts of acetylene black, 0.4-0.6 parts of barium sulfate, 3-4 parts of sulfuric acid, 12-14 parts of water, and 55-60 parts of lead powder.
[0026] Example 1. A paste additive for a lead-acid battery plate of the present embodiment comprises graphene and nano silicon powder, wherein the amount of graphene added is 0.12% by weight of the lead powder of the positive electrode lead paste and 0.1% by weight of the lead powder of the negative electrode lead paste; the amount of nano silicon powder added is 0.53% by weight of the lead powder of the positive electrode lead paste and 0.5% by weight of the lead powder of the negative electrode lead paste.
[0027] The graphene of this embodiment is multi-layer graphene with a thickness of less than 10 nm, in which carbon atoms are tightly stacked in an ABC manner to form a benzene ring structure; The purity of nano silicon powder reaches more than 99.999%, the particle size is evenly distributed at 2nm, and the specific surface area is 800m 2 above.
[0028] The graphene of this embodiment is also treated with a modifying liquid, and the specific treatment method is as follows: Add 1 part of silane coupling agent, 2 parts of yttrium oxide and 2 parts of nano calcium carbonate to 5 parts of regulator and stir evenly to obtain a modified liquid; add graphene to a sufficient amount of the modified liquid and stir for modification treatment, filter and dry after stirring.
[0029] The stirring speed of the stirring modification treatment in this embodiment is 450 r / min, and the stirring is for 1 hour.
[0030] The silane coupling agent of this embodiment is silane coupling agent KH550.
[0031] The regulating solution of this embodiment uses 1 part of sodium silicate solution, 2 parts of lanthanum chloride solution and 2 parts of nano titanium dioxide.
[0032] The mass fraction of the sodium silicate solution in this embodiment is 2%; the mass fraction of the lanthanum chloride solution is 4%.
[0033] The positive electrode lead paste of this embodiment includes 50 parts of lead powder, 2 parts of sulfuric acid, 15 parts of water, 2 parts of red lead, and 4 parts of carbon fiber.
[0034] The negative electrode lead paste of this embodiment is prepared from the following raw materials by weight: 0.1 parts of lignin, 0.2 parts of acetylene black, 0.4 parts of barium sulfate, 3 parts of sulfuric acid, 12 parts of water, and 55 parts of lead powder.
[0035] Example 2. A paste additive for a lead-acid battery plate of the present embodiment comprises graphene and nano silicon powder, wherein the amount of graphene added is 0.22% by weight of the lead powder of the positive electrode lead paste and 0.2% by weight of the lead powder of the negative electrode lead paste; the amount of nano silicon powder added is 0.65% by weight of the lead powder of the positive electrode lead paste and 0.6% by weight of the lead powder of the negative electrode lead paste.
[0036] The graphene of this embodiment is multi-layer graphene with a thickness of less than 10 nm, in which carbon atoms are tightly stacked in an ABC manner to form a benzene ring structure; The purity of nano silicon powder reaches more than 99.999%, the particle size is evenly distributed at 4nm, and the specific surface area is 800m 2 above.
[0037] The graphene of this embodiment is also treated with a modifying liquid, and the specific treatment method is as follows: Add 3 parts of silane coupling agent, 4 parts of yttrium oxide and 3 parts of nano calcium carbonate to 8 parts of regulator and stir evenly to obtain a modified liquid; add graphene to a sufficient amount of the modified liquid and stir for modification treatment, filter and dry after stirring.
[0038] The stirring speed of the stirring modification treatment in this embodiment is 550 r / min, and the stirring is for 1 hour.
[0039] The silane coupling agent of this embodiment is silane coupling agent KH550.
[0040] The regulating solution of this embodiment uses 3 parts of sodium silicate solution, 4 parts of lanthanum chloride solution and 4 parts of nano titanium dioxide.
[0041] The mass fraction of the sodium silicate solution in this embodiment is 5%; the mass fraction of the lanthanum chloride solution is 7%.
[0042] The positive electrode lead paste of this embodiment includes 55 parts of lead powder, 3 parts of sulfuric acid, 16 parts of water, 5 parts of red lead, and 7 parts of carbon fiber.
[0043] The negative electrode lead paste of this embodiment is prepared from the following raw materials by weight: 0.2 parts of lignin, 0.3 parts of acetylene black, 0.6 parts of barium sulfate, 4 parts of sulfuric acid, 14 parts of water, and 60 parts of lead powder.
[0044] Example 3. A paste additive for a lead-acid battery plate of the present embodiment comprises graphene and nano silicon powder, wherein the amount of graphene added is 0.18% by weight of the lead powder of the positive electrode lead paste and 0.15% by weight of the lead powder of the negative electrode lead paste; the amount of nano silicon powder added is 0.60% by weight of the lead powder of the positive electrode lead paste and 0.55% by weight of the lead powder of the negative electrode lead paste.
[0045] The graphene of this embodiment is multi-layer graphene with a thickness of less than 10 nm, in which carbon atoms are tightly stacked in an ABC manner to form a benzene ring structure; The purity of nano silicon powder reaches more than 99.999%, the particle size is evenly distributed at 3nm, and the specific surface area is 800m 2 above.
[0046] The graphene of this embodiment is also treated with a modifying liquid, and the specific treatment method is as follows: Add 2 parts of silane coupling agent, 3 parts of yttrium oxide and 2.5 parts of nano calcium carbonate to 6.5 parts of regulator and stir evenly to obtain a modified liquid; add graphene to a sufficient amount of the modified liquid and stir for modification treatment, filter and dry after stirring.
[0047] The stirring speed of the stirring modification treatment in this embodiment is 500 r / min, and the stirring is for 1 hour.
[0048] The silane coupling agent of this embodiment is silane coupling agent KH550.
[0049] The conditioning solution of this embodiment uses 2 parts of sodium silicate solution, 3 parts of lanthanum chloride solution and 3 parts of nano titanium dioxide.
[0050] The mass fraction of the sodium silicate solution in this embodiment is 3.5%; the mass fraction of the lanthanum chloride solution is 5.5%.
[0051] The positive electrode lead paste of this embodiment includes 52.5 parts of lead powder, 2.5 parts of sulfuric acid, 15.5 parts of water, 3.5 parts of red lead, and 5.5 parts of carbon fiber.
[0052] The negative electrode lead paste of this embodiment is prepared from the following raw materials by weight: 0.15 parts of lignin, 0.25 parts of acetylene black, 0.5 parts of barium sulfate, 3.5 parts of sulfuric acid, 13 parts of water, and 57.5 parts of lead powder.
[0053] Comparative Example 1. The difference from Example 3 is that the graphene is not treated with a modifying liquid.
[0054] Comparative Example 2. The difference from Example 3 is that yttrium oxide and nano-calcium carbonate are not added to the modified solution.
[0055] Comparative Example 3. The difference from Example 3 is that no nano titanium dioxide is added to the regulator.
[0056] Comparative Example 4. The difference from Example 3 is that no sodium silicate solution is added to the regulator.
[0057] Comparative Example 5. The difference from Example 3 is that no lanthanum chloride solution is added to the regulator.
[0058] In order to compare and illustrate the performance of different products, the following properties of the products obtained in the embodiments and comparative examples were tested, and the test results are as follows.
[0059] The product performance tests of Examples 1-3 and Comparative Examples 1-5 are as follows:
[0060] It can be seen from Comparative Examples 1-5 and Example 3 that the product of Example 3 has excellent discharge capacity and number of cycles. At the same time, the product uses the modified liquid obtained by combining the specific regulator of the present invention with yttrium oxide and nano-calcium carbonate to improve graphene, and the product performance effect is the most significant. Using other methods instead is not as obvious as the effect of the present invention.
[0061] Graphene and nano silicon powder are added to the plates as additives for lead-acid battery plate paste to make double-nano plates to produce lead-acid batteries. The plates and paste are then cured to form double nanocrystals. The double nanocrystals can significantly inhibit the formation of sulfuric acid crystals, inhibit the adsorption of lead sulfate crystals to form larger crystals and crystal films, thereby ensuring the static formation effect of incompletely formed batteries, reducing battery internal resistance, increasing the battery card CCA, and reducing the battery self-discharge rate. The conversion of lead sulfate into a cycle when the battery is installed on a vehicle is almost completely reversible, greatly improving the charge and discharge acceptance capacity and cycle life, further meeting the demand of contemporary consumers for long-life batteries.
[0062] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0063] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A paste additive for lead-acid battery plates, characterized in that: It contains graphene and nano silicon powder, wherein the added amount of graphene is 0.12-0.22% of the weight of the positive electrode lead paste and lead powder, and 0.1%-0.2% of the weight of the negative electrode lead paste and lead powder; the added amount of nano silicon powder is 0.53-0.65% of the weight of the positive electrode lead paste and lead powder, and 0.5%-0.6% of the weight of the negative electrode lead paste and lead powder.
2. The lead-acid battery plate paste additive according to claim 1, characterized in that: The graphene is multi-layer graphene with a thickness of less than 10 nm, in which carbon atoms are tightly stacked in an ABC manner to form a benzene ring structure; The purity of nano silicon powder reaches more than 99.999%, the particle size is evenly distributed in 2~4nm, and the specific surface area is 800m 2 above.
3. The paste additive for lead-acid battery plates according to claim 1, characterized in that: The graphene is also treated with a modification liquid, and the specific treatment method is as follows: Add 1-3 parts of silane coupling agent, 2-4 parts of yttrium oxide and 2-3 parts of nano calcium carbonate to 5-8 parts of regulator and stir evenly to obtain modified liquid; add graphene to a sufficient amount of modified liquid and stir for modification treatment, filter and dry after stirring.
4. The paste additive for lead-acid battery plates according to claim 3, characterized in that: The stirring speed of the stirring modification treatment is 450-550 r / min, and the stirring is for 1 hour.
5. The paste additive for lead-acid battery plates according to claim 3, characterized in that: The silane coupling agent is silane coupling agent KH550.
6. The paste additive for lead-acid battery plates according to claim 3, characterized in that: The regulating solution comprises 1-3 parts of sodium silicate solution, 2-4 parts of lanthanum chloride solution and 2-4 parts of nano titanium dioxide.
7. A paste additive for lead-acid battery plates according to claim 6, characterized in that: The mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the lanthanum chloride solution is 4-7%.
8. The lead-acid battery plate paste additive according to claim 1, characterized in that: The positive electrode lead paste comprises 50-55 parts of lead powder, 2-3 parts of sulfuric acid, 15-16 parts of water, 2-5 parts of red lead and 4-7 parts of carbon fiber.
9. The paste additive for lead-acid battery plates according to claim 1, characterized in that: The negative electrode lead paste is prepared from the following raw materials by weight: 0.1-0.2 parts of lignin, 0.2-0.3 parts of acetylene black, 0.4-0.6 parts of barium sulfate, 3-4 parts of sulfuric acid, 12-14 parts of water, and 55-60 parts of lead powder.
Citation Information
Cited By
Positive lead paste of lead storage battery as well as preparation method and application of positive lead paste
CN122202305A
